Influence of light curing source on microhardness of composite resins of different shades - Briso, André Luiz Fraga [UNESP]; Fedel, Tânia Maria [UNESP]; Pereira, Sibéria de Morais [UNESP]; Mauro, Silvio José [UNESP]; Sundfeld, Renato Herman [UNESP]; Sundefeld, Maria Lúcia Marçal Mazza [UNESP] (FapUNIFESP (SciELO), 2006)
Introduction: The evolution of light curing units can be noticed by the different systems recently introduced. The technology of LED units promises longer lifetime, without heating and with production of specific light for activation of camphorquinone. However, further studies are still required to check the real curing effectiveness of these units. Purpose: This study evaluated the microhardness of 4 shades (B-0.5, B-1, B-2 and B-3) of composite resin Filtek Z-250 (3M ESPE) after light curing with 4 light sources, being one halogen (Ultralux - Dabi Atlante) and three LED (Ultraled - Dabi Atlante, Ultrablue - DMC and Elipar Freelight - 3M ESPE). Methods: 192 specimens were distributed into 16 groups, and materials were inserted in a single increment in cylindrical templates measuring 4mm x 4mm and light cured as recommended by the manufacturer. Then, they were submitted to microhardness test on the top and bottom aspects of the cylinders. Results: The hardness values achieved were submitted to analysis of variance and to Tukey test at 5% confidence level. It was observed that microhardness of specimens varied according to the shade of the material and light sources employed. The LED appliance emitting greater light intensity provided the highest hardness values with shade B-0.5, allowing the best curing. On the other hand, appliances with low light intensity were the least effective. It was also observed that the bottom of specimens was more sensitive to changes in shade. Conclusion: Light intensity of LED light curing units is fundamental for their good functioning, especially when applied in resins with darker shades.
Keywords: Composite resins; Curing equipment; Microhardness; Shades